2020
DOI: 10.1061/(asce)ee.1943-7870.0001830
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in Detroit Wastewater

Abstract: Untreated wastewater samples were collected from the Great Lakes Water Authority (GLWA) Water Resource Recovery Facility (WRRF) located in southeast Michigan between April 8 and May 26, 2020. The WRRF is the largest single-site wastewater treatment facility in the US, and it receives wastewater from its service area via three main interceptors: Detroit River Interceptor (DRI), North Interceptor-East Arm (NI-EA), and Oakwood-Northwest-Wayne County Interceptor (O-NWI). A total of 54 untreated wastewater samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 8 publications
4
40
0
Order By: Relevance
“…3). Therefore, there is a correlation between the amount of SARS-CoV-2 in wastewater and the hospitalization data, as observed by other authors 7,11,23,24 . However, few studies have reported long-term monitoring (over several months) of SARS-CoV-2 in wastewater 11,25 .…”
Section: Resultssupporting
confidence: 71%
“…3). Therefore, there is a correlation between the amount of SARS-CoV-2 in wastewater and the hospitalization data, as observed by other authors 7,11,23,24 . However, few studies have reported long-term monitoring (over several months) of SARS-CoV-2 in wastewater 11,25 .…”
Section: Resultssupporting
confidence: 71%
“…Although much can be learned from existing literature on virus detection in environmental matrices ( Haramoto et al., 2018 ; Ye et al., 2016 ), the rapid onset of COVID-19 presented a number of challenges for implementation of wastewater surveillance, particularly in identifying suitable methods for detection and quantification of SARS-CoV-2 (an enveloped RNA virus) in a complex, solids-rich matrix. Numerous studies have reported detection and/or quantification of SARS-CoV-2 genetic material in untreated wastewater ( Ahmed et al., 2020 ; Gonzalez et al., 2020 ; Green et al., 2020 ; Medema et al., 2020 ; Miyani et al., 2020 ; Nemudryi et al., 2020 ; Sherchan et al., 2020 ; Wu et al., 2020b ), treated wastewater ( Wurtzer et al., 2020 ), and wastewater-associated solids ( Peccia et al., 2020 ). However, the methods in these early studies vary widely, potentially confounding comparisons across studies.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Since the onset of the coronavirus pandemic in 2019, research groups worldwide have demonstrated the feasibility and scalability of monitoring severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in wastewater or sludge to track and/or predict the transmission and control of SARS-CoV-2 in sewered communities. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Given the widespread efforts on wastewater sampling brought by these SARS-CoV-2 surveillance platforms, co-analysis of human biomarkers in wastewater for substance use assessment represents an attractive strategy to gain additional insights into population behavior and health status underlying the susceptibility to coronavirus disease 2019 (COVID- 19) and its adverse outcomes. Indeed, recent reviews and meta-analyses have highlighted common risk factors for COVID-19 and substance use.…”
Section: Introductionmentioning
confidence: 99%